2021
DOI: 10.1136/bmjopen-2020-043421
|View full text |Cite
|
Sign up to set email alerts
|

Examining Australian’s beliefs, misconceptions and sources of information for COVID-19: a national online survey

Abstract: ObjectivePublic cooperation to practise preventive health behaviours is essential to manage the transmission of infectious diseases such as COVID-19. We aimed to investigate beliefs about COVID-19 diagnosis, transmission and prevention that have the potential to impact the uptake of recommended public health strategies.DesignAn online cross-sectional survey.ParticipantsA national sample of 1500 Australian adults with representative quotas for age and gender provided by an online panel provider.Main outcome mea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…While the knowledge score was good overall, there were some gaps with respect to the less frequent symptoms of COVID-19. More concerning is the misconception that antibiotics could be an effective way to prevent COVID-19 among 47.9% of the respondents, a finding similar to that found in a study which reported that as high as 66.4% of Australians believe that taking antibiotics regularly could possibly prevent COVID-19 ( 34 ). The proliferation of information over social media, including misinformation, could be a factor in this observation as well as in promoting risky behavior ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 66%
“…While the knowledge score was good overall, there were some gaps with respect to the less frequent symptoms of COVID-19. More concerning is the misconception that antibiotics could be an effective way to prevent COVID-19 among 47.9% of the respondents, a finding similar to that found in a study which reported that as high as 66.4% of Australians believe that taking antibiotics regularly could possibly prevent COVID-19 ( 34 ). The proliferation of information over social media, including misinformation, could be a factor in this observation as well as in promoting risky behavior ( 35 , 36 ).…”
Section: Discussionsupporting
confidence: 66%
“…Concurrently, this study found that the respondents had a poor understanding of the sources of COVID-19 infection, the transmission routes, and the symptoms of infected people. Public information campaigns and educational interventions could improve the overall awareness of infectious-disease-prevention knowledge [ 26 ]. Thus, relevant government departments should strengthen knowledge dissemination regarding the epidemiological characteristics of COVID-19 and training regarding symptom recognition, especially for people with low education levels.…”
Section: Discussionmentioning
confidence: 99%
“…, 2021; Chen et al. , 2021; Gerosa et al , 2021; Mohammed et al , 2021; Savolainen, 2021; Thomas et al , 2021; Wang et al , 2021) and coronavirus health literacy (Bray et al , 2021; Okan et al , 2020; Sykes et al. , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%